Lens material and formulation of multipurpose solutions affects contact lens disinfection - Santos, Lívia (2011)
Purpose To assess the disinfection efficacy of multipurpose solutions (MPS) against different bacterial species adhered either to silicon hydrogel or to conventional hydrogel contact lenses (CLs). The influences of the MPS formulation and the chemical composition of the lens material were investigated. Methods This investigation followed the standard 14729, which establishes the guidelines for assessing CL disinfecting solutions. Two commercially available (Opti-Free® Express® and Renu® Multiplus) solutions and one recalled solution (Complete® MoisturePlus™) were used in this study. After disinfection, the number of survivors was estimated by the colony forming units’ method. Results The lens material appears to influence disinfection. The conventional hydrogel polymacon exhibited the highest disinfection scores, a fact that should be related with the lack of electrostatic attraction towards the biocides and its hydrophilicity. The MPS formulation appears to have influence in disinfection efficacy as well. For most adhered bacteria, Opti-Free® was capable of reducing cell concentration in 4-log. Conclusion Disinfection results from multivariate factors and this study confirmed that the lens material and the MPS play a very important role in the disinfection efficacy of CL.